Protein-Protein Interactions Modulate the Docking-Dependent E3-Ubiquitin Ligase Activity of Carboxy-Terminus of Hsc70-Interacting Protein (CHIP) - Narayan, Vikram; Landré, Vivien; Ning, Jia; Hernychova, Lenka; Muller, Petr; Verma, Chandra; Walkinshaw, Malcolm D; Blackburn, Elizabeth A; Ball, Kathryn L (Molecular and cellular proteomics, 2015)
CHIP is a tetratricopeptide repeat (TPR) domain protein that functions as an E3-ubiquitin ligase. As well as linking the molecular chaperones to the ubiquitin proteasome system, CHIP also has a docking-dependent mode where it ubiquitinates native substrates, thereby regulating their steady state levels and/or function. Here we explore the effect of Hsp70 on the docking-dependent E3-ligase activity of CHIP. The TPR-domain is revealed as a binding site for allosteric modulators involved in determining CHIP's dynamic conformation and activity. Biochemical, biophysical and modeling evidence demonstrate that Hsp70-binding to the TPR, or Hsp70-mimetic mutations, regulate CHIP-mediated ubiquitination of p53 and IRF-1 through effects on U-box activity and substrate binding. HDX-MS was used to establish that conformational-inhibition-signals extended from the TPR-domain to the U-box. This underscores inter-domain allosteric regulation of CHIP by the core molecular chaperones. Defining the chaperone-associated TPR-domain of CHIP as a manager of inter-domain communication highlights the potential for scaffolding modules to regulate, as well as assemble, complexes that are fundamental to protein homeostatic control.
Keywords: Tumor Suppressor Protein p53; proteiny tepelného šoku HSP70; Kinetics; lymfocyty; Cell Line, Tumor; ubikvitinace; Protein Structure, Tertiary; vazebná místa; vazba proteinů; terciární struktura proteinů; lidé; mapování interakce mezi proteiny; Models, Molecular; Protein Interaction Mapping; Protein Structure, Secondary; molekulární modely; HSP70 Heat-Shock Proteins; alosterická regulace; proteasomový endopeptidasový komplex; ubikvitinligasy; Interferon Regulatory Factor-1; nádorový supresorový protein p53; Ubiquitination; sekundární struktura proteinů; Gene Expression; exprese genu; Lymphocytes; interferonový regulační faktor 1; Allosteric Regulation; Proteasome Endopeptidase Complex; Ubiquitin-Protein Ligases; Protein Binding; kinetika; nádorové buněčné linie; Binding Sites; Humans